2018
DOI: 10.1136/bjophthalmol-2017-311802
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of avoidable blindness in Papua New Guinea: a nationwide survey

Abstract: PNG has one of the highest reported prevalence of blindness globally. Cataract and uncorrected refractive error are the main causes, suggesting a need for increased accessible services with improved resources and advocacy for enhancing eye health literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 18 publications
1
26
0
1
Order By: Relevance
“…Results of RAAB study have been reported elsewhere 7. As diabetes was predicted to be a concerning issue in PNG urban areas, the DR assessment was only completed in the NCD region.…”
Section: Methodsmentioning
confidence: 99%
“…Results of RAAB study have been reported elsewhere 7. As diabetes was predicted to be a concerning issue in PNG urban areas, the DR assessment was only completed in the NCD region.…”
Section: Methodsmentioning
confidence: 99%
“…Among the 446 participants with an expert examination indicating VA greater than +0. 5 participants with VA results ≤+0.5 logMAR were recommended to the local eye clinics for follow-up examinations, only 24.7% (19/77) went to the clinic for further examination 6 months later. Table 3 shows the demographic information of family screeners from 523 household.…”
Section: Resultsmentioning
confidence: 99%
“…Trachoma was not mentioned in this study [ 35 ]. During a Rapid Assessment of Avoidable Blindness in PNG, one case of trachomatous corneal opacity was found among 4818 survey participants aged ≥50 years from across the country, accounting for 0.8% of cases of blindness [ 36 ].…”
Section: Resultsmentioning
confidence: 99%